The institution-growth nexus in Sub-Saharan Africa: new evidence from heterogeneous panel causality approach - ÇOKGEZEN, MURAT (SPRINGER HEIDELBERG, 2022)
Whether economic growth is the cause or the consequence of improved institutional quality has been a controversial issue. To throw light on this debate, the present study aims to investigate the nature and direction of causality between institutional quality and economic growth. To this end, a panel data of 30 SSA countries for the 1990-2015 period is used and analyzed using a heterogeneous panel non-causality approach developed by Dumitrescu and Hurlin (Econ Model 29(4):1450-1460, 2012). Our empirical findings indicate a significant heterogeneity across the countries with regard to the relationship between growth and institutional quality, based on the income level. In low-income countries, we found a unidirectional causality that runs from institutional quality to growth. For lower-middle-income countries, however, the direction of causality is reversed. The evidence from this study also suggests a bidirectional causality in upper-middle-income countries. The policy implication of these findings is that policymakers in low-income countries should focus on institutional reform. Good quality institutions will promote economic growth that will ultimately turn into a cyclical process between economic growth and institutional development in later stages.
Keywords: Institutional quality; Economic growth; SSA; Heterogonous panel causality; ECONOMIC-GROWTH; GRANGER CAUSALITY; COUNTRIES